2019
DOI: 10.3390/ijms20010150
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to Mesenchymal Transition in Human Mesothelial Cells Exposed to Asbestos Fibers: Role of TGF-β as Mediator of Malignant Mesothelioma Development or Metastasis via EMT Event

Abstract: Asbestos exposure increases the risk of asbestosis and malignant mesothelioma (MM). Both fibrosis and cancer have been correlated with the Epithelial to Mesenchymal Transition (EMT)—an event involved in fibrotic development and cancer progression. During EMT, epithelial cells acquire a mesenchymal phenotype by modulating some proteins. Different factors can induce EMT, but Transforming Growth Factor β (TGF-β) plays a crucial role in promoting EMT. In this work, we verified if EMT could be associated with MM de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…Many genes associated with reprogramming of cell–cell and cell–extracellular matrix interactions orchestrated by means of the EMT process are differentially expressed in MPM and correlate with worse survival. Interestingly, a substantial number of these genes such as matrix metalloproteases ( MMP3 , MMP7 , and MMP14 ), integrins, and a group of cytoskeletal proteins and cell adhesion molecules ( ITGA3 , ITGB4 , VCAN , VIM , PECAM1 , CDH1 , CDH5 , and CD44 ), structural molecules, and modifiers of ECM ( LOXL2 , BNC1 , GREM-1 , FBN2 , THBS2 , RASGRP3 , ANXA6 , ADAMTS6 , and ADAM19 ) and transcription factors ( SNAI1 , SNAI2 , ZEB1 , TWIST1 , and HMGA2 ) are either significantly enriched in the gene signature or recognized as signaling modulators of the TGF-β (transforming growth factor β) pathway [ 19 , 62 , 112 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. Indeed, a large body of evidence that accumulated over the last few years, suggests that the TGF-β signaling pathway is dysregulated in MPM.…”
Section: Genomics Of Malignant Pleural Mesotheliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes associated with reprogramming of cell–cell and cell–extracellular matrix interactions orchestrated by means of the EMT process are differentially expressed in MPM and correlate with worse survival. Interestingly, a substantial number of these genes such as matrix metalloproteases ( MMP3 , MMP7 , and MMP14 ), integrins, and a group of cytoskeletal proteins and cell adhesion molecules ( ITGA3 , ITGB4 , VCAN , VIM , PECAM1 , CDH1 , CDH5 , and CD44 ), structural molecules, and modifiers of ECM ( LOXL2 , BNC1 , GREM-1 , FBN2 , THBS2 , RASGRP3 , ANXA6 , ADAMTS6 , and ADAM19 ) and transcription factors ( SNAI1 , SNAI2 , ZEB1 , TWIST1 , and HMGA2 ) are either significantly enriched in the gene signature or recognized as signaling modulators of the TGF-β (transforming growth factor β) pathway [ 19 , 62 , 112 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. Indeed, a large body of evidence that accumulated over the last few years, suggests that the TGF-β signaling pathway is dysregulated in MPM.…”
Section: Genomics Of Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…Indeed, a large body of evidence that accumulated over the last few years, suggests that the TGF-β signaling pathway is dysregulated in MPM. Thereof, a less favorable prognostic association has been identified between the EMT score of MPM and the activated TGF-β gene signature [ 119 , 123 ]. Taken together, further studies may provide the basis for assessing TGF-β pathway-specific inhibitors for targeted therapy in MPM, at least in those with high EMT scores.…”
Section: Genomics Of Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…TGFb plays a crucial role in promoting EMT. 20 TGF-b was used to induce brosis of HFL-1 cells. The results showed that TGFb promoted migration of HFL-1 cells compared with control group.…”
Section: Pd Inhibits Emt In Pulmonary Brosismentioning
confidence: 99%
“…To monitor the potency of encapsulation on EMT and stemness acquisition, we also performed real-time PCR analysis. 17 Data showed that the expression of three genes Snail, Vimentin and Zeb were increased 7 days after encapsulation of HT-29 cells with Alg and PLL compared to the control cells expanded on the plastic surface (P < 0.05; Figure 2b). Of note, the use of Alg microspheres loaded with PLL could significantly upregulate all genes (Figure 2b).…”
Section: Microencapsulation Increased Emt Ratementioning
confidence: 94%